Epidemiology of Cryptococcal antigenemia among HIV infected patients in southwestern Nigeria - Odekunle Bola Odegbemi; Hannah Odunola Dada-Adegbola; Ikeola Adejoke Adeoye; Samuel Adetona Fayemiwo (University of New South Wales, 2019)
Cryptococcosis is a life-threatening fungal infection that presents diversely with no specific pathognomonic features. Cryptococcal disease is one of the most important opportunistic infections, and a significant contributor to early mortality in HIV infected subjects. Cryptococcal antigenemia occurs in Nigeria, but the magnitude of this disease remains unclear. This study was carried out to determine the prevalence of CrAg among HIV infected and HIV seronegative subjects and to assess the relationship between CD4 count and CrAg in HIV-positive subjects attending Adeoyo Maternity Teaching Hospital, Yemetu, Ibadan. In an hospital-based case-control study using simple random sampling, 114 HIV-seropositive individuals (cases) and 228 HIV-seropositive individuals (controls) were recruited. A semi-structured interviewer-administered questionnaire was used to collect data from subjects and retrospective review of CD4 count records in HIV infected subjects. Five millilitres of venous blood were collected from each participant. Serum Cryptococcal antigen testing was done using CrAg Lateral Flow Assay. Data was analyzed using descriptive statistics and bivariate analysis at 5% level of significance. Mean age of cases was 41.2 ± 10.0 years and 85 (74.6%) were females while mean age of controls was 38.9 ± 13.7 years and 156 (68.4%) were females. The prevalence of CrAg among cases was 11.4% and 7.0% among controls. Cases were about two times more likely to test positive for CrAg. However, the association was not statistically significant (OR: 1.71, 95%CI: 0.79 - 3.68). Individuals with CD4 counts of ≤100 cells/µl were 20 times more likely to have positive serum cryptococcal antigen than individuals with CD4 counts >100 cells/µl (OR: 20.3, 95%CI: 5.23-78.9). This study has demonstrated significant prevalence of Cryptococcal antigenemia among the study population; however, prevalence was higher among cases. Screening for CrAg should therefore be part of routine tests amongst all confirmed HIV seropositive cases, since asymptomatic cryptococcal antigenemia predicts impending cryptococcal infection with probable mortality.